Pengaruh Organization Culture Dan Komitmen Organisasi Terhadap Employee Performance Dimoderasi Motivasi Individu - James Jacky Wayoi; Antyo Pracoyo; Enny Haryanti; Subarjo Joyosumarto (STIE Indonesia Banking School, 2025)
This study examines the effect of organizational culture and organizational commitment on employee performance, with individual motivation as a moderating variable at PT. Bank Papua Biak Branch. The population consisted of 57 employees, including permanent, contract (PKWT), and interns, with sampling conducted using a non-probability technique. Data were analyzed using Moderated Regression Analysis (MRA). Results show that organizational culture has a positive and significant effect on employee performance, indicating that stronger culture leads to higher performance. Meanwhile, organizational commitment has a positive but insignificant effect, suggesting that commitment alone is not sufficient to improve outcomes. Individual motivation strengthens the link between culture and performance, as motivated employees reinforce the role of culture in enhancing results. However, motivation does not moderate the relationship between commitment and performance. Based on these findings, management is advised to reinforce organizational culture through training, value dissemination, and exemplary leadership. Organizational commitment can be improved through participatory management, while motivation should be supported by fair rewards, career opportunities, recognition, and a positive work environment. Future studies are encouraged to explore other moderating variables, such as job satisfaction, organizational climate, or leadership style, for more comprehensive insights.